Attentional characteristics of junior taekwondo athletes during the training phase - Makhroja, Ersa; Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (UIR Press, 2026)
Background: Attentional control is a critical psychological factor influencing performance in combat sports such as taekwondo. However, limited research has examined attentional characteristics of junior athletes during the training phase, particularly within the Indonesian context. Objectives: This study aimed to describe the attentional characteristics of junior taekwondo athletes during training. Methods: A descriptive cross-sectional design was employed involving 30 athletes aged 14–16 years. Attentional characteristics were assessed using the Test of Attentional and Interpersonal Style (TAIS). Data were analysed using descriptive statistics (mean and standard deviation), and gender differences were explored descriptively. Results: Male athletes demonstrated slightly higher scores in the information processing dimension (M = 56.29, SD = 11.66) compared to female athletes (M = 52.20, SD = 11.05). However, overall differences between groups were small, indicating relatively comparable attentional profiles. Across dimensions, most athletes demonstrated moderate levels of attentional control. Conclusion: Junior taekwondo athletes exhibited generally moderate attentional characteristics during the training phase. Although minor differences were observed between genders, these were not substantial. Future research should employ larger samples and inferential analysis to better understand factors influencing attentional development.